QSAR Study on Inhibitors of Enzyme Ribonucleoside Diphosphate Reductase - Prakash Singh, Ved; Nath Dhar, Durga; Kumar Srivastava, Ravi (Asian Journal of Chemistry, 2010)
Descriptors heat of formation, energy of HOMO, total energy, absolute hardness and chemical potential in different combination, have been used to develop QSAR models of inhibitors of enzyme ribonucleoside diphosphate reductase. The inhibitors are mainly derivatives of 2-formylpyridine thiosemicarbazone and 1-formylpyridine thiosemicarbazone. The derivatives of 2-formylpyridine thiosemicarbazone have been devided into two sets, on the basis of difference in position of substituents and the derivatives of 1-formylpyridine thiosemicarbazone have also been divided in two sets, on the basis of difference of inhibitory activity. One QSAR model having the best predictive power is presented in each set. The correlation coefficient value is above 0.9 in first, third and fourth set and above 0.79 in second set. The best combinations of descriptors are heat of formation, total energy and energy HOMO.